1975
DOI: 10.1021/ja00844a045
|View full text |Cite
|
Sign up to set email alerts
|

Azetidinone antibiotics. XII. Chemical transformations of penicillins and cephalosporins. Mechanism and stereochemistry of the interconversions of penam and cepham systems

Abstract: Isomeric penam and cepham compounds have been prepared and isolated. I t has been established that a thiiranium ion is a common intermediate in the interconversions of penam and cepham systems. The mechanism and stereochemistry of these interconversions have been studied in detail. A new synthesis of deacetoxycephalosporin starting from substituted penams and cephams is reported

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1975
1975
1996
1996

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Subsequently, a 1,3-trans-ring attack of the S-atom at C(3) takes place, the C1-atom being released and an episulfonium ion 9 formed. Contraction from a six-to five-membered ring via an episulfonium intermediate was previously observed in the synthetic interconversion of cepham and penam systems [32]. Baertschi et al [I51 previously considered the formation of this type of intermediate in the degradation of cefaclor (1) in an acidic medium.…”
Section: Co2-mentioning
confidence: 95%
“…Subsequently, a 1,3-trans-ring attack of the S-atom at C(3) takes place, the C1-atom being released and an episulfonium ion 9 formed. Contraction from a six-to five-membered ring via an episulfonium intermediate was previously observed in the synthetic interconversion of cepham and penam systems [32]. Baertschi et al [I51 previously considered the formation of this type of intermediate in the degradation of cefaclor (1) in an acidic medium.…”
Section: Co2-mentioning
confidence: 95%
“…The structure is based on elemental analysis and spectral data obtained for 5a and for its methyl and benzyl ester (5b and 5c). The NMR spectra showed a coupling constant of 14.5 Hz for the geminal CH2, which is a typical value for a halocepham structure14,15) (the 2J value for an isomeric halogenopenam is about 12 Hz14,15)) The assumed /3-bromo configuration is based on mechanistic considerations discussed by KUKOLJA et al 16) and the reaction is supposed to be similar to that described by KAMIYA et a1.17) These authors obtained a mixture of a 2-chloromethylpenam and 3c upon treatment of 2c with pyridine-HCI and pyridine in tetrachloroethane. The cepham structure proposed for 5a is not in disagreement with the experiment described by KAMIYA et al, since it is known16, 17) that 2-bromopenams easily rearrange into the more stable 3-bromocephams.…”
mentioning
confidence: 89%
“…One of us [7] has suggested that biosynthesis of penicillin N (S), deacetoxycephalosporin C(9), and closely related substances could possibly be explained as proceeding via a common thiiranium ion (10) (Ra = (2-amino-6-adipyl)amino, R = H; see Scheme). The formation of the final products most likely depends upon conditions in fermentation processes.…”
mentioning
confidence: 99%
“…Some other peaks indicated that other unidentified species had been formed. When a fresh solution of the P-sulfoxide 4 was prepared, it was found that the C(2) resonance disappeared within [5][6][7][8] hours. These changes suggest that in the case of the P-sulfoxide 4 there is a rapid tautomeric exchange of the C(2) protons for deuterium.…”
mentioning
confidence: 99%